Seasonal and plant-part isotopic and biochemical variation in Posidonia oceanica - CRESSON, PIERRE; BOUDOURESQUE, CHARLES FRANÇOIS; RUITTON, SANDRINE; CASALOT, LAURIE; VERLAQUE, MARC; HARMELIN-VIVIEN, MIREILLE (Mediterranean Marine Science, 2019)
Posidonia oceanica is an iconic and highly productive Mediterranean seagrass. As most studies focused on the fate of this production, temporal and plant part-specific variations of isotopic composition and biochemical content were overlooked. Combined seasonal and plant-part stable isotope composition and biochemical concentrations were measured at the lower depth limit of a P. oceanica meadow ( 25 meter depth), and explained by previous knowledge of the specific metabolic functioning of each part. The predominance of compounds with complex chemical structure was reflected by the high concentrations of insoluble carbohydrates, high C/N ratios, and high δ13C values. Plant parts clustered in 3 groups with similar isotopic or biochemical features and metabolism: rhizomes and juvenile leaves, intermediate and adult leaves, senescent and drifting leaves. This result agrees with the vegetative phenology of the plant. The biochemical composition and the isotopic composition of the plant parts were consistent with previous knowledge about the photosynthetic activity and its seasonal variation. Correlations were found between N-linked descriptors (δ15N and protein content), and between δ13C and insoluble carbohydrate concentration. Epibiont values differed considerably from those of the leaf, as this community is taxonomically diverse and seasonally variable. Biochemical and isotopic composition measured confirmed that the current complex metabolism of P. oceanica results from adaptations to the specific life in a marine oligotrophic environment.